EXPERIMENTAL STUDY ON FRETTING FATIGUE OF 2024 ALUMINUM ALLOY UNDER ALTERNATING NORMAL LOAD (MT) - ZHANG YuXuan; LI Xin; YANG JianWei; TIAN Shuai; LIU LeQiang (Jixie qiangdu)
Fretting fatigue failure of 2024 aluminum alloy under alternating normal load was investigated. A biaxial fretting fatigue test system is designed which can apply alternating phase load and distal load. Through Abaqus finite element analysis, the normal loading device of the test bench was analyzed and calculated, and the influence of the force conduction error and the swing angle of the fretting pad on the test accuracy was investigated, the accuracy of loading test machine is verified. The influence of phase difference of 0°, 45° and 90° on fatigue life of 2024 aluminum alloy under alternating normal load was studied. The test results show that the life of 2024 aluminum alloy specimens increases with the increase of phase difference. Through the analysis of wear state, it is found that the influence of wear is small when the phase difference is 0° and 45°, and the life increases with the increase of phase difference. When the phase difference is 90°, the wear is more serious. Under the joint action of wear and fatigue damage, the fatigue life of specimens at 90° phase difference is further increased. The overall trend of fretting fatigue life of specimens under alternating normal load is that the life increases with the increase of phase difference, and the wear increases with the increase of phase difference.